“Caras Pintadas”: a juventude estudantil em 1992 e suas imagens em movimento - Coelho, Lívia Maria (2021)
This work intends to historically comprehend the youth action and the organized student’s movement in the development and articulation of the events known as “Caras Pintadas” (CP). This political movement appears in academical papers mostly through journalistic points of view and/or being considered as a social movement, or even as a strictly university student’s movement, organized by the União Nacional dos Estudantes (UNE). This dissertation intends an analysis that understand the Cara Pintada movement as a student’s movement, built by high school students and college students, who possess their own agenda as such. Also, studies the movement constitution in parallel with the President Fernando Collor’s impeachment investigation and the student’s activities along the protests, their actions, symbols, and innovative ways of social contestation. Part of the analysis focus on how mass medias showed the movement and how these communication vehicles played a role in the characterization of caras-pintadas. To do so, different documents were utilized, as magazines, papers, and television news report between July/1991 and July/1993, as well as documentaries that mentioned the theme. The results about the movement points to the innovative youth aspect of musicality, parody, and enjoyment during the destitution process of the Brazilian President